ISLAMIZATION, SHIA, AND IRAN: The Historical Background of Shia-Iran Sensitive Issues - Arafah Pramasto (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2020)
After the Syrian civil war broke out in the year 2011, many news outlets around the world have accused the Iranian Shia regime of interfering in the region by means of promoting sectarian violence. The chain of issues can be tracked back to emergence of Iran as an Islamic Republic in 1979 after which many countries including Pakistan and Indonesia feared revolutions like Iran. This resulted in negative perceptions of the Iranian regime. This Research shows that negative perceptions about the current Iranian regime among many Sunnite-Majority countries exist because of past conflicts between the Sunnite and the Shia. Islamization of present-day Iran or Persia in the past along with spread of Islam in Iran by Arabs in the early days of Islam has always caused conflicts between Arabs and Persians e.g. Shiasization of Persia under Shah Ismail I of Safavid Dynasty and atrocities against Sunnis.[Setelah perang saudara Suriah pecah pada tahun 2011, banyak outlet berita di seluruh dunia menuduh rezim Syiah-Iran mencampuri wilayah tersebut dengan cara mempromosikan kekerasan sektarian. Rantai masalah dapat dilacak kembali pada kemunculan Iran sebagai Republik Islam pada tahun 1979 setelah banyak negara, termasuk Pakistan dan Indonesia, takut pada revolusi seperti Iran. Ini menghasilkan persepsi negatif tentang rezim Iran. Penelitian ini menunjukkan bahwa persepsi negatif tentang rezim Iran saat ini di antara banyak negara mayoritas Suni ada karena konflik masa lalu antara Suni dan Syiah. Islamisasi Iran di masa kini atau Persia di masa lalu yang bersamaan dengan penyebaran Islam di Iran oleh orang Arab di masa awal Islam selalu menyebabkan konflik antara orang Arab dan Persia seperti Syiasisasi Persia di bawah Shah Ismail I dari Dinasti Safawi dan kekejaman terhadap orang-orang Suni]